GAMBARAN MOTIVASI DAN PERAN ORANGTUA TENTANG CUCI TANGAN PAKAI SABUN PADA ANAK DI SD NEGERI 19 KOTA JAMBI TAHUN 2019 - Della Febriana; Arifarahmi Arifarahmi; Ria Febrina (Universitas Baiturrahim, 2019)
One indicator of clean and healthy living behavior is washing hands with soap. Washing hands with soap is one of the most effective ways to prevent diarrheal diseases and acute respiratory infections. Data from public health Office in Jambi city 2017, the number of diarrhea in Jambi city was 3,745 people. The public health center Simpang Kawat is the public health center which has a large number of diarrhea fourth highest of 20 the public health center in Jambi city as many as 182 people one of schools in the public health center Simpang Kawat area is SD N 19 Jambi city. This study used descriptive method to determine the description of motivation and the role of parents about washing hands with soap on students at SD N 19 Jambi city year 2019. It was conducted at SD N 19 Jambi city on August 06th 2019. Populations were students class VI as many as 45 students. Samples used Total Sampling technique. The instrument used questionnaire. The collecting of data used questionnaire and analyzed as univariate. The findings indicated that from 45 respondents most of them have good motivation that is 24 respondents (53.3%) and 26 respondents (57.8%) have good role of parents. Most of respondents have good motivation and good role of parents. For the personals of school to provide complete facilities and infrastructure that are used for students in schools so they can wash their hands with soap.